2007
DOI: 10.1111/j.1525-142x.2007.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating paedomorphic heterochrony in trilobites: the case of the diminutive trilobite Flexicalymene retrorsa minuens from the Cincinnatian Series (Upper Ordovician), Cincinnati region

Abstract: Flexicalymene retrorsa minuens from the uppermost 3 m of the Waynesville Formation of the Cincinnatian Series (Upper Ordovician) of North America lived approximately 445 Ma and exhibited marked reduction in maximum size relative to its stratigraphically subjacent sister subspecies, Flexicalymene retrorsa retrorsa. Phylogenetic analysis is consistent with the notion that F. retrorsa retrorsa was the ancestor of F. retrorsa minuens. F. retrorsa minuens has been claimed to differ from F. retrorsa retrorsa"in size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Numerous studies cover small morphological structures using a low number of landmarks and their results seem to be satisfactory, when an adequate set of landmarks is available over only half of the anatomical element shape (e.g. Hughes & Chapman, 1995;Kim et al 2002Kim et al , 2009Hunda & Hughes, 2007;Webster, 2007).…”
Section: C Biometric Quantification Of Sclerite Outlinesmentioning
confidence: 99%
“…Numerous studies cover small morphological structures using a low number of landmarks and their results seem to be satisfactory, when an adequate set of landmarks is available over only half of the anatomical element shape (e.g. Hughes & Chapman, 1995;Kim et al 2002Kim et al , 2009Hunda & Hughes, 2007;Webster, 2007).…”
Section: C Biometric Quantification Of Sclerite Outlinesmentioning
confidence: 99%
“…Phenotypic plasticity in the developmental pathway is an important mode of evolution for many marine organisms (e.g., Hunda and Hughes 2007;Nielsen 2008). Heterochronic phenotypic variation has been reported for several species.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the relevance of geometric morphometrics to assess morphological diversity of trilobites. In calymenid trilobites in particular, Hunda and Hughes (2007) studied the species Flexicalymene retrorsa (Foerste, 1910) and Chestnut (2008) worked on Silurian calymenids. Finally, Delabroye and Cronier (2008) recently studied the ontogeny of the Armorican trinucleid trilobite Marrolithus bureaui (Oehlert, 1895) using a landmark-based approach.…”
Section: Introductionmentioning
confidence: 99%